Gambaran Kadar Serum Glutamic Pyruvic Transminase (SGPT) pada Petugas Stasiun Pengisian Bahan Bakar Umum (SPBU) di Kota Jambi - Muslina Muslina; Aminahtun Latifah; Dewi Kurniasih (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Gas stations (SPBU) as distributors of refined fuel oil (BBM) are one source of air pollution. SPBU workers are a group of people who are vulnerable to Plumbum (Pb) exposure. The toxic effects of lead can affect the function of organs, such as the liver. In this case SGPT (Serum Glutamic Pyruvate Transaminase) which is an enzyme found in many liver cells is known to be effective for diagnosing hepatocellular destruction. And this study aims to see an overview of SGPT levels in gas station workers at Jambi City. The method used in this research is descriptive with a total of 30 samples from gas station workers. The SGPT examination method used is the enzymatic colometry test. The data will be analyzed and presented in the form of a frequency distribution table. The results of a study found 7 samples of high SGPT levels in men while in women there were no high levels of SGPT. In addition, high levels of SGPT were found mostly in the age category > 30 years (13.3%) and working time over 5 years. Based on the results of examining SGPT levels at gas station workers, 30 samples were examined, 23 people with normal results and 7 people with high results.